1996
DOI: 10.1023/a:1016063719541
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: When particle size is properly selected, these emulsions could be promising and effective as an injectable carrier for lipophilic antitumor agents in order to enhance the tumor delivery and efficacies while reducing toxicities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The potential pharmaceutical applications include use as a carrier for lipophilic drugs [7][8][9][10][11] and for site-specific drug delivery by attaching ligands for various cell surface receptors to the particle surface. 12) Generally, intravenous emulsions are biodegradable, biocompatible, physically stable, easy to scale up and cost effective when compared to other drug carriers.…”
mentioning
confidence: 99%
“…The potential pharmaceutical applications include use as a carrier for lipophilic drugs [7][8][9][10][11] and for site-specific drug delivery by attaching ligands for various cell surface receptors to the particle surface. 12) Generally, intravenous emulsions are biodegradable, biocompatible, physically stable, easy to scale up and cost effective when compared to other drug carriers.…”
mentioning
confidence: 99%
“…Studies have revealed larger sized droplets (>250 nm compared to <100 nm) were cleared faster from the body, indicating a great role of mononuclear phagocyte system (MPS) in the clearance of these nanoemulsion [29]. Moreover, droplet size has also been demonstrated to determine the intratumor distribution versus the peripheral tissues [30]. Therefore, it is in common agreement that nanoemulsions with mean droplet size of less than 150 nm and a narrow, unimodal distribution is highly favored.…”
Section: Nanoemulsionmentioning
confidence: 94%